CD34+ cell therapy significantly reduces adverse cardiac events, health care expenditures, and mortality in patients with refractory angina. (12th June 2020) - Johnson, Grace L.; Henry, Timothy D.; Povsic, Thomas J.; Losordo, Douglas W.; Garberich, Ross F.; Stanberry, Larissa I.; Strauss, Craig E.; Traverse, Jay H.
Abstract: Patients with refractory angina who are suboptimal candidates for further revascularization have improved exercise time, decreased angina frequency, and reduced major adverse cardiac events with intramyocardial delivery of CD34 + cells. However, the effect of CD34 + cell therapy on health care expenditures before and after treatment is unknown. We determined the effect of CD34 + cell therapy on cardiac-related hospital visits and costs during the 12 months following stem cell injection compared with the 12 months prior to injection. Cardiac-related hospital admissions and procedures were retrospectively tabulated for patients enrolled at one site in one of three double-blinded, placebo-controlled CD34 + trials in the 12 months before and after intramyocardial injections of CD34 + cells vs placebo. Fifty-six patients were randomized to CD34 + cell therapy (n = 37) vs placebo (n = 19). Patients randomized to cell therapy experienced 1.57 ± 1.39 cardiac-related hospital visits 12 months before injection, compared with 0.78 ± 1.90 hospital visits 12 months after injection, which was associated with a 62% cost reduction translating to an average savings of $5500 per cell therapy patient. Patients in the placebo group also demonstrated a reduction in cardiac-related hospital events and costs, although to a lesser degree than the CD34 + group. Through 1 January 2019, 24% of CD34 + subjects died at an average of 6.5 ± 2.4 years after enrollment, whereas 47% of placebo patients died at an average of 3.7 ± 1.9 years after enrollment. In conclusion, CD34 + cell therapy for subjects with refractory angina is associated with improved mortality and a reduction in hospital visits and expenditures for cardiac procedures in the year following treatment. : Abstract : The total cardiovascular hospitalizations, procedures and emergency room visits are significantly reduced in patients with refractory angina in the 12 months following intramyocardial CD34 + progenitor cell injections compared to the 12 months prior to injections ( P = .002).